2013
DOI: 10.1155/2013/828329
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of 188-Rhenium-Labeled Antibody to Melanin in Patients with Metastatic Melanoma

Abstract: There is a need for effective “broad spectrum” therapies for metastatic melanoma which would be suitable for all patients. The objectives of Phase Ia/Ib studies were to evaluate the safety, pharmacokinetics, dosimetry, and antitumor activity of 188Re-6D2, a 188-Rhenium-labeled antibody to melanin. Stage IIIC/IV metastatic melanoma (MM) patients who failed standard therapies were enrolled in both studies. In Phase Ia, 10 mCi 188Re-6D2 were given while unlabeled antibody preload was escalated. In Phase Ib, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…In support of these results, we have already shown that a high dose of Listeria at or 188 Re is less toxic in humans than chemotherapy (11)(12)(13). Currently, other Listeria constructs are available with reduced pathogenicity and used for different approaches.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In support of these results, we have already shown that a high dose of Listeria at or 188 Re is less toxic in humans than chemotherapy (11)(12)(13). Currently, other Listeria constructs are available with reduced pathogenicity and used for different approaches.…”
Section: Discussionsupporting
confidence: 53%
“…Using medical internal radiation dose formalism, we have estimated that the dose delivered to the tumor by RL was ∼30 Gy, which is within a tumoricidal range for internal radionuclide therapy (5). (11)(12)(13), the combination of Listeria at and radioactivity has never been tested for its safety in vivo. Therefore, we performed various experiments aimed at testing RL safety, such as biodistribution of RL, free 188 Re, and Listeria at ; pathology; and liver functions.…”
Section: Listeriamentioning
confidence: 99%
“…However, preclinical and clinical studies have not determined the impact of RIT on stem cells. Encouraged by the promising results in a clinical trial with 188 Re-labeled anti-Melanin MAb 6D2 (IgM) in patients with metastatic melanomas, 53 Jandl et al evaluated the effect of 188 Re-6D2 on the stem cells in a preclinical xenograft model. 54 As compared to untreated controls, the 188 Re-6D2 treated animals had a fourfold decrease in tumor size.…”
Section: Targeting Stem Cells With Radiolabeled Antibodiesmentioning
confidence: 99%
“…To test this hypothesis, we used data on biodistribution of 188 Re-labeled antibody to melanin in athymic melanoma xenograft-bearing mice (6,7).…”
mentioning
confidence: 99%